The influence of a modified lipopolysaccharide O-antigen on the biosynthesis of xanthan in Xanthomonas campestris pv. campestris B100. Issue 1 (December 2016) - Steffens, Tim; Vorhölter, Frank-Jörg; Giampà, Marco; Hublik, Gerd; Pühler, Alfred; Niehaus, Karsten
Abstract Background The exopolysaccharide xanthan is a natural product which is extensively used in industry. It is a thickening agent in many fields, from oil recovery to the food sector. Xanthan is produced by the Gram negative bacteriumXanthomonas campestris pv. campestris (Xcc). We analyzed the lipopolysaccharide (LPS) of three mutant strains of the Xcc wild type B100 to distinguish if the xanthan production can be increased when LPS biosynthesis is affected. Results The Xcc B100 O-antigen (OA) is composed of a linear main chain of rhamnose residues with N-acetylfucosamine (FucNAc) side branches at every second rhamnose. It is the major LPS constituent. The O-antigen was missing completely in the mutant strain H21012 (deficient inwxcB ), since neither rhamnose nor FucNAc could be detected as part of the LPS by MALDI-TOF-MS, and only a slight amount of rhamnose and no FucNAc was found by GC analysis. The LPS of two other mutants was analyzed, Xcc H28110 (deficient inwxcK ) and H20110 (wxcN ). In both of them no FucNAc could be detected in the LPS fraction, while the rhamnose moieties were more abundant than in wild type LPS. The measurements were carried out by GC and confirmed by MALDI-TOF-MS analyses that indicated an altered OA in which the branches are missing, while the rhamnan main chain seemed longer than in the wild type. Quantification of xanthan confirmed our hypothesis that a missing OA can lead to an increased production of the extracellular polysaccharide. About 6.3 g xanthan per g biomass were produced by the Xcc mutant H21012 (wxcB ), as compared to the wild type production of approximately 5 g xanthan per g biomass. In the two mutant strains with modified OA however, Xcc H28110 (wxcK ) and Xcc H20110 (wxcN ), the xanthan production of 5.5 g and 5.3 g, respectively, was not significantly increased. Conclusions Mutations affecting LPS biosynthesis can be beneficial for the production of the extracellular polysaccharide xanthan. However, only complete inhibition of the OA resulted in increased xanthan production. The inhibition of the FucNAc side branches did not lead to increased production, but provoked a novel LPS phenotype. The data suggests an elongation of the linear rhamnan main chain of the LPS OA in both the Xcc H28110 (wxcK ) and Xcc H20110 (wxcN ) mutant strains.